ANALISIS PENGARUH BENTUK LUBANG TERHADAP KARAKTERISTIK PERPINDAHAN PANAS PADA MENARA PENDINGIN TIPE PLAT DATAR BERLUBANG BERTINGKAT - Mustika, Yulanda Dwi; Syuhada, Ahmad; Razali , Razali (Jurnal Rekayasa Mesin, 2024)
Cooling tower is one of the most widely used cooling systems in the industrial world. A cooling tower is a series of heat exchange devices that use working fluids, such as water and air, to act as a cooling medium by coming into direct contact with the air, causing a small portion of the water to evaporate and reducing the temperature of the liquid. To enhance the performance of cooling towers, many researchers have conducted studies on this matter, but there is still room for improvement to achieve more optimal results. The objective of this research is to obtain an optimal cooling tower system by determining the convective heat transfer coefficient. With this phenomenon, the research investigates the heat transfer process that occurs on perforated plates in a flat plate-type cooling tower with an overall tower height of approximately 2.4 meters and around 5 levels of fluid distribution media. The length of each plate is 0.7 meters with a width of 0.5 meters. Variations are also made in the multi-level cooling tower design, specifically in the shape of the perforations used, including circular, triangular, and square perforation shapes, using a zig-zag outlet hole model. The perforated plate area is 0.0157 square meters for each plate, with a 15° inclination angle for each plate arrangement. The research results indicate that the highest heat transfer coefficient values occur in the multi-level cooling tower when using square-shaped plates, followed by triangular-shaped plates, while circular-shaped plates have the lowest heat transfer coefficient values. Therefore, variations in the shape of the perforations on the flat plates affect the change in temperature reduction and the heat transfer coefficient values in the performance of the multi-level cooling tower.